2020
DOI: 10.1155/2020/8697651
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maternal Satisfaction and Associated Factors among Parturients Who Underwent Cesarean Delivery under Spinal Anesthesia at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2019

Abstract: Background. Spinal anesthesia is the most common anesthetic technique for cesarean delivery. Patient satisfaction is a subjective and complicated concept, involving physical, emotional, psychological, social, and cultural factors. Regular evaluation of maternal satisfaction related to anesthesia service is an important parameter to the required changes and expansion of high-quality care services. We aimed to assess maternal satisfaction and associated factors among parturients who underwent cesarean delivery u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The predictors of the former level were a single spinal attempt, successful block, less level of PDPH, and prophylactic antiemetic. The type of surgery for the latter was only elective cesarean section [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predictors of the former level were a single spinal attempt, successful block, less level of PDPH, and prophylactic antiemetic. The type of surgery for the latter was only elective cesarean section [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal satisfaction to current practice of preoperative anesthesia evaluation who received fasting instruction, Informed regarding PONV and type of anesthesia given were higher compared there counterpart similar to previous findings [ 15 , 16 ].Furthermore, a study found that an effective perioperative evaluation by the anesthetist had increased maternal satisfaction [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that there is various level of maternal satisfaction with spinal anesthesia in delivery care which ranged from 50-95% in developing and developed countries respectively. Maternal satisfaction rate reports were higher in high-setup countries, whereas satisfaction of mothers in low setups, like some African countries, is slightly not good; only 51.9-87.2% of mothers' were satis ed with spinal anesthesia during C/S delivery services in some sub-Saharan countries (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 95%